Digitalization of Companies Prospects for Process Automation Using RPA and GPT Integration - Fitriani, Widia; Nasution, Mhd. Irsan; Supratikta, Hadi (Indonesian Development of Economics and Administration Journal, 2024)
The aim of this article is to organize the concepts related to the digitalization of modern enterprises and identify potential directions of digitalization in automation processes using the integration of RPA and GPT technologies. As a research method, this article uses a review of the literature over the last 20 years and presents a case study. The first part of this article reviews the concepts of digitalization and process automation. A distinction was made in the understanding of these terms, which became the basis for explaining the possibility of integrating GPT with RPA. Key prospects for using ChatGPT are then identified, and limitations are discussed. The possible use of GPT integration with RPA is illustrated with a case study of a service company in the green energy sector, demonstrating the potential of combining GPT with RPA.